2021
DOI: 10.1021/acs.chemmater.1c03402
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Reaction Phase Diagram for the Penetration Etching/Growth of Graphene Adlayers

Abstract: Cu has shown an advantage in growing monolayer graphene due to the very low C solubility and surface-mediated self-limiting growth, which hinders the growth of multilayer graphene. This work reports an unconventional penetration etching/growth of graphene adlayers tuned by oxygen beyond the self-limiting growth, supported by the C isotope labeling results. The effect of oxygen is nonmonotonic, i.e., with the increase of oxygen, graphene adlayers are etched without damaging the top layer, then shift to growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In bilayer or multilayer graphene synthesis, the growth methods are varied. Shen et al [87] reported that a certain amount of oxygen during growth [80] Copyright 2018, American Chemical Society. c) SEM micrographs of graphene grown at 100 °C with 100% full coverage.…”
Section: Thickness-controlled Multilayer Graphene Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In bilayer or multilayer graphene synthesis, the growth methods are varied. Shen et al [87] reported that a certain amount of oxygen during growth [80] Copyright 2018, American Chemical Society. c) SEM micrographs of graphene grown at 100 °C with 100% full coverage.…”
Section: Thickness-controlled Multilayer Graphene Growthmentioning
confidence: 99%
“…Shen et al. [ 87 ] reported that a certain amount of oxygen during growth will tune the growth of adlayers beyond the self‐limited growth of the first layer. In this method, they achieve the growth of 90% coverage of uniform bilayer graphene.…”
Section: Thickness‐controlled Multilayer Graphene Growthmentioning
confidence: 99%
“…This explains that the thickness of graphene increases with the introduction of oxygen and decreases from the center to the edge. However, an overdosed oxygen may take C away by forming CO or CO 2 or may be other –C x O y H z species, [ 14 ] which also reduces the supply of C to the front side. As a result, the further increase of oxygen reduces the C supply at the center and the maximum C concentration moves away from the center, leading to the ring‐like distribution of graphene thickness (Figure 2a,b, the top three samples).…”
Section: Resultsmentioning
confidence: 99%
“…[7,8] When appropriate parameters are used, few-layer graphene (<10) can also be grown on Cu, normally in an inverted wedding cake mode, [9][10][11] and the C precursors to the layers under the top layer can be supplied by crossing graphene island edge side (side diffusion mode), [12] diffusing through the Cu foil from the other side (backside diffusion mode), [13] and penetrating the top layer assisted with oxygen. [14] When adding other elements such as Ni and Si to form alloys, few-layer graphene with even better uniformity and stacking order can be achieved. [15,16] However, the thickness of graphene is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation